2011
DOI: 10.1111/j.1399-0039.2010.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

‐174G/C interleukin‐6 gene polymorphism and the risk of transplanted kidney failure or graft loss during a 5‐year follow‐up period

Abstract: The influence of cytokine gene polymorphisms on transplanted kidney outcome is not well understood. The aim of this one-centre study was to analyse the association between tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-10, interferon-γ (IFN-γ) and transforming growth factor-β1 (TGF-β1) genotypes and the incidence of delayed graft function (DGF), acute rejection (AR) and 5-year kidney graft loss. Genotyping was performed in 199 subsequent kidney graft recipients from deceased donors without inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In transplantation, blocking IL-6 leads to decreased IFN-γ and IL-17 mRNA, reduced alloantigen-stimulated T cell proliferation, increased proportion of Treg, and prolonged allograft survival in mouse models 202-204 . In humans, IL-6 is associated with acute and chronic rejections and IL-6 levels correlate with the degree of inflammation in the allografts 205-210 . The use of tocilizumab with intravenous immunoglobulin in sensitized kidney transplant patients shows improved donor-specific antibody levels similar to the results obtained in a mouse model 211,212 .…”
Section: Impact Of Alternative Immunosuppressive Agents On Tregmentioning
confidence: 99%
“…In transplantation, blocking IL-6 leads to decreased IFN-γ and IL-17 mRNA, reduced alloantigen-stimulated T cell proliferation, increased proportion of Treg, and prolonged allograft survival in mouse models 202-204 . In humans, IL-6 is associated with acute and chronic rejections and IL-6 levels correlate with the degree of inflammation in the allografts 205-210 . The use of tocilizumab with intravenous immunoglobulin in sensitized kidney transplant patients shows improved donor-specific antibody levels similar to the results obtained in a mouse model 211,212 .…”
Section: Impact Of Alternative Immunosuppressive Agents On Tregmentioning
confidence: 99%
“…28 Studies on the impact of recipient À174 G/C polymorphism on acute rejection following renal transplantation have provided conflicting results. One study found a lower frequency of G/G or G/C genotype in recipients who developed acute rejection, 29 while another found a higher frequency of these genotypes, 30,31 although the results of these studies were not statistically significant. High levels of the G/G and G/C IL-6 promoter genotypes have been shown to be significantly associated with decreased risk of acute rejection following liver transplant.…”
Section: Discussionmentioning
confidence: 88%
“…As for ethnicity, 7 were studies of Caucasians [9], [22], [23], [27], [28], [37], 3 studies were of Asians [19]–[21], and 4 studies of mixed ethnicity [13], [18], [26], [29]. Regarding the immunosuppressive protocols, patients were uniformly prescribed with CsA in 5 studies[18]–[20], [23], [29] while in the remaining 9 studies were applied with either CsA or FK506[9], [13], [21], [22], [24][28] (Table 1). …”
Section: Resultsmentioning
confidence: 99%